👤

II. Solve and show your solution

Direction: Factor the following polynomials

11. x3 -27

12. 6x²y² + 3xy³ - 3xy²

13. x² - y²

14. ac – ad + bc – bd

15. x² - 10xy + 25y²

16. 4x² + 12x + 9

17. 2x² - x – 10

18. x² + x - 12

19. 4x² - 9

20. mr – nr + ms – ns​


Sagot :

Answer:

11.) (x-3)(+3x+9)

12.) 3xy²(2x+y-1)

13.) (x+y)(x-y)

14.) (c+d)(a+b)

15.) (x-5y)²

16.) (2x+3)²

17.) (2x-5)(x+2)

18.) (x-3)(x+4)

19.) (4x-3) (4x+3)

20.) (m-n)(r-s)

Step-by-step explanation:

yn na po Yung answers

hope it helps

Answer:

11. (x - 3) (x²+3x+9)

12.3xy²(2x+y-1)

13.(x+y)(x-y)

14.(could not simplify further)

15.(x-5y)²

16.(2x+3)²

17.(x+2)(2x-5)

18. (I don't know how to solve sorry)

19.(2x+3)(2x-3)

20.(could not simplify further)

Step-by-step explanation:

11. = x³ - 27

= x³-3³

= (x - 3) (x²+3x+3²)

= (x - 3) (x²+3x+9)

12.= 6x²y²+3xy³-3xy²

= 6xy²+3xy²y-3xy²

= 3xy²+3xy²y-3xy²

= 3xy²(2x+y-1)

13.= x²-y²

= (x+y)(x-y)

14. (could not simplify further)

15.= x²-10xy+25y²

= 25y²=(5y)²

= -10xy=2x • 5y

= x²-2x • 5y +(5y)²

= (x-5y)²

16.= 4x²+12x+9

= 4x²=(2x)²

= 9=3²

= 12x=2•2x•3

= (2x)²+2•2x•3+3²

= (2x+3)²

17. = 2x²-x-10

= (2x²+4x)+(-5x-10)

Factor out 2x from 2x²+4x: 2x(x+2)

factor out -5 from -5-10: -5(x+2)

= 2x(x+2)-5(x+5)

= (x+2)(2x-5)

18. I don't know how to solve sorry

19. = 4x²-9

= (2x)² - 3²

= (2x+3)(2x-3)

20. (could not simplify further)